SARS-CoV-2, Zika viruses and mycoplasma: Structure, pathogenesis and some treatment options in these emerging viral and bacterial infectious diseases - Ferreira, Gonzalo; Santander, Axel; Savio, Florencia; Guirado, Mariana; Sobrevia, Luis [UNESP]; Nicolson, Garth L. (Elsevier, 2021)
The molecular evolution of life on earth along with changing environmental, conditions has rendered mankind susceptible to endemic and pandemic emerging infectious diseases. The effects of certain systemic viral and bacterial infections on morbidity and mortality are considered as examples of recent emerging infections. Here we will focus on three examples of infections that are important in pregnancy and early childhood: SARS-CoV-2 virus, Zika virus, and Mycoplasma species. The basic structural characteristics of these infectious agents will be examined, along with their general pathogenic mechanisms. Coronavirus infections, such as caused by the SARS-CoV-2 virus, likely evolved from zoonotic bat viruses to infect humans and cause a pandemic that has been the biggest challenge for humanity since the Spanish Flu pandemic of the early 20th century. In contrast, Zika Virus infections represent an expanding infectious threat in the context of global climate change. The relationship of these infections to pregnancy, the vertical transmission and neurological sequels make these viruses highly relevant to the topics of this special issue. Finally, mycoplasmal infections have been present before mankind evolved, but they were rarely identified as human pathogens until recently, and they are now recognized as important coinfections that are able to modify the course and prognosis of various infectious diseases and other chronic illnesses. The infectious processes caused by these intracellular microorganisms are examined as well as some general aspects of their pathogeneses, clinical presentations, and diagnoses. We will finally consider examples of treatments that have been used to reduce morbidity and mortality of these infections and discuss briefly the current status of vaccines, in particular, against the SARS-CoV-2 virus. It is important to understand some of the basic features of these emerging infectious diseases and the pathogens involved in order to better appreciate the contributions of this special issue on how infectious diseases can affect human pregnancy, fetuses and neonates.
Keywords: Bacteria; Infection; Morbidity; Pregnancy; Reproduction; Virus